Metacognitive awareness, Process Science and Chemistry Student Learning Outcomes Divergent and Convergent in PBL - Yusran Khery (Jurnal Pendidikan Sains, 2013)
Kesadaran Metakognitif, Proses Sains, dan Hasil Belajar Kimia Mahasiswa Divergen dan Konvergen dalam PBL Abstract: The aim of this study are: (1) determine differences in metacognitive awareness and cognitive learning outcomes of students with PBL and conventional strategies; (2) determine differences in metacognitive awareness, science process skills, and cognitive learning outcomes between students with divergent thinking and convergent character that learned by PBL strategy. This study uses three kinds of designs are descriptive study design, quasi-experimental design and pre-experimental design to answer the research objectives. Instruments used in this research are: (1) questionnaire characters divergent thinking and convergent; (2) metacognitive awareness questionnaire; (3) observation sheets science process skills; and (4) tests the cognitive learning. Data were analyzed by inferential statistics. The results showed that: (1) there is no difference in metacognitive awareness and cognitive learning outcomes of students who gained from learning with PBL strategies and conventional strategies; (2) there is no difference metacognitive awareness and cognitive learning outcomes among students of divergent and convergent. Science process skills of students diverging better than converging. Key Words: metacognitive awareness, the process of science, learning outcomes, the characters think, PBL Abstrak: Tujuan dari penelitian ini adalah: (1) mengetahui perbedaan kesadaran metakognitif dan hasil belajar kognitif mahasiswa dengan strategi PBL dan konvensional; (2) mengetahui perbedaan kesadaran metakognitif, keterampilan proses sains, dan hasil belajar kognitif antara mahasiswa dengan karakter berpikir divergen dan konvergen yang dibelajarkan dengan strategi PBL. Penelitian ini menggunakan tiga macam rancangan yaitu rancangan penelitian deskriptif, rancangan eksperimental semu dan rancangan pra eksperimental untuk menjawab tujuan penelitian. Instrumen yang digunakan dalam penelitian adalah: (1) angket karakter berpikir divergen dan konvergen; (2) angket kesadaran metakognitif; (3) lembar observasi keterampilan proses sains; dan (4) tes hasil belajar kognitif. Data dianalisis secara statistik inferensial. Hasil penelitian menunjukkan bahwa: (1) tidak terdapat perbedaan kesadaran metakognitif dan hasil belajar kognitif mahasiswa yang diperoleh dari pembelajaran dengan strategi PBL dan strategi konvensional; (2) tidak terdapat perbedaan kesadaran metakognitif dan hasil belajar kognitif antara mahasiswa divergen dan konvergen. Keterampilan proses sains mahasiswa divergen lebih baik dibandingkan dengan yang konvergen.Kata kunci: kesadaran metakognitif, proses sains, hasil belajar, karakter berpikir, PBL